1989
DOI: 10.1111/j.1530-0277.1989.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Beef Fat Prevents Alcoholic Liver Disease in the Rat

Abstract: The amount and type of dietary fat is thought to be important in the pathogenesis of alcoholic liver disease (ALD). We investigated the role of different dietary fats in our rat model for ALD. Liver pathology was evaluated in rats fed ethanol and lard or tallow or corn oil over a period of 2 to 6 months. All experimental animals were pair-fed the same diet as controls except that glucose was isocalorically replaced by ethanol. Rats fed tallow and ethanol developed none of the features of ALD, those fed lard an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
143
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(146 citation statements)
references
References 17 publications
2
143
0
1
Order By: Relevance
“…Histological examination was carried out by a pathologist who had no prior knowledge of the dietary groups. The liver pathology score was calculated as follows 15,16 : steatosis (the percentage of liver cells containing fat): 1ϩ, less than 25% of cells containing fat; 2ϩ, 26% to 50%; 3ϩ, 51% to 75%; and 4ϩ, more than 75%; inflammation and necrosis: one focus/lobule, 1ϩ; two or more foci/lobule, 2ϩ. The total liver pathology score was calculated by adding the scores from each of the parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological examination was carried out by a pathologist who had no prior knowledge of the dietary groups. The liver pathology score was calculated as follows 15,16 : steatosis (the percentage of liver cells containing fat): 1ϩ, less than 25% of cells containing fat; 2ϩ, 26% to 50%; 3ϩ, 51% to 75%; and 4ϩ, more than 75%; inflammation and necrosis: one focus/lobule, 1ϩ; two or more foci/lobule, 2ϩ. The total liver pathology score was calculated by adding the scores from each of the parameters.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of epidemiologic observations relating the type of dietary fat to ALD, 14 studies in the intragastric feeding model have shown that rats fed saturated fat with ethanol develop none of the histologic features of ALD, whereas rats fed polyunsaturated fatty acids (PUFA) with ethanol show fatty liver, necrosis, inflammation, and fibrosis. 15,16 In particular, rats fed fish oil (a very rich source of PUFA) with ethanol develop more severe liver injury than rats fed corn oil and ethanol. 17,18 When palm oil is fed with ethanol, the rats develop only fatty liver with no necrosis or inflammation.…”
mentioning
confidence: 99%
“…Liver pathology was scored as described by Nanji et al (26) as follows: steatosis (the percentage of liver cells containing fat): Ͻ25% ϭ 1ϩ; Ͻ50% ϭ 2ϩ; Ͻ75% ϭ 3ϩ; Ͼ75% ϭ 4ϩ; inflammation and necrosis: 1 focus per low-power field ϭ 1ϩ; 2 or more ϭ 2ϩ. One point was given for each grade of severity of histological abnormality and a total score was calculated for each liver.…”
Section: Pathological Evaluationmentioning
confidence: 99%
“…19,20 In this model, we and other investigators have shown that an inverse relationship exists between the saturation of lipids in the diet and the severity of alcohol-induced liver injury. [21][22][23][24] Rats fed ethanol and diets enriched in saturated fatty acids are protected from liver injury, whereas diets enriched in polyunsaturated fatty acids promote alcoholic liver injury. Thus, the rat intragastric feeding model, in which ethanol is fed with different dietary fats, is useful to elucidate the pathogenesis of alcoholic liver disease.…”
mentioning
confidence: 99%